The Effect of Story Telling on Anxiety in Preschool Children in the Action of Infusion at Bhayangkara Hospital Makassar - Sunarti Sunarti; Yusnita Ismail (An Idea Health Journal, 2021)
Nursing actions in children, generally require invasive measures (infusion). Infusion is a medical procedure that causes a lot of anxiety in pediatric patients. One way to reduce anxiety in children is to use storytelling therapy. The purpose of this study was to determine the effect of storytelling on preschool children's anxiety in the infusion procedure at Bhayangkara Hospital Makassar. This type of research is a pre-experimental research with a one group pretest-posttest design approach. The determination of the sample was carried out by purposive sampling technique with a sample size of 32 respondents. The effect test was carried out using a paired sample T-test with a significance level of <0.05. The results showed that before doing story telling the anxiety of pre-school age children was moderate anxiety (40.6%) and severe anxiety (59.4%), children's anxiety after storytelling, moderate anxiety (78.1%) and severe anxiety. (21.9%). There is an effect of storytelling on the anxiety of preschoolers during the infusion in the emergency room at Bhayangkara Hospital Makassar, the p value = 0.000 (?<0.05). The conclusion of this study is that there is a significant effect of storytelling on the anxiety of preschoolers during the infusion in the emergency room at Bhayangkara Hospital Makassar. Therefore, it is expected that nurses in the emergency room can apply story telling during the infusion in preschool children.